2020
DOI: 10.1128/jcm.01629-19
|View full text |Cite
|
Sign up to set email alerts
|

High Agreement Between an Ultrasensitive Clostridioides difficile Toxin Assay and a C. difficile Laboratory Algorithm Utilizing GDH-and-Toxin Enzyme Immunoassays and Cytotoxin Testing

Abstract: The Singulex Clarity C. diff toxins A/B (Clarity) assay is an automated, ultrasensitive immunoassay for the detection of Clostridioides difficile toxins in stool. In this study, the performance of the Clarity assay was compared to that of a multistep algorithm using an enzyme immunoassay (EIA) for detection of glutamate dehydrogenase (GDH) and toxins A and B arbitrated by a semiquantitative cell cytotoxicity neutralization assay (CCNA). The performance of the assay was evaluated using 211 residual deidentified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…C. difficile produces metabolically inactive endospores, making it is resistant to gastric acid and most kinds of antibiotics [21]. C. difficile can produce two toxins: enterotoxin A and cytotoxin B [22]. The pathogenicity of C. difficile is based on the fact that at least one of the two toxins acts as a glycosyltransferase to modify guanosine triphosphatases in intestinal epithelial cells and cause the disruption of the actin cytoskeleton [23].…”
Section: Resultsmentioning
confidence: 99%
“…C. difficile produces metabolically inactive endospores, making it is resistant to gastric acid and most kinds of antibiotics [21]. C. difficile can produce two toxins: enterotoxin A and cytotoxin B [22]. The pathogenicity of C. difficile is based on the fact that at least one of the two toxins acts as a glycosyltransferase to modify guanosine triphosphatases in intestinal epithelial cells and cause the disruption of the actin cytoskeleton [23].…”
Section: Resultsmentioning
confidence: 99%
“…Using the same toxin cutoff as in the Hansen article, the study demonstrated high agreement with the testing algorithm [55 ▪ ]. The authors concluded that the Singulex Clarity assay is a stand-alone testing solution for the diagnosis of C. difficile [55 ▪ ]. Unfortunately, the company decided not to pursue commercial application of the Clarity assay.…”
Section: Future Diagnostic Approachesmentioning
confidence: 90%
“…In a multicenter study evaluating the Clarity automated assay using the manufacturers’ toxin cutoff of 12 pg/ml of stool, Hansen et al [54] demonstrated a positive percent agreement after discrepant analysis of 96.3% and a negative percent agreement of 93.3% compared with CCNA as the reference method. In a recent single center study by Landry et al [55 ▪ ] the authors compared the Clarity assay with a standard of care testing algorithm using GDH and toxin EIA arbitrated by CCNA. Using the same toxin cutoff as in the Hansen article, the study demonstrated high agreement with the testing algorithm [55 ▪ ].…”
Section: Future Diagnostic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an automated ultrasensitive toxin assay was approved by US Food and Drug Administration, which showed comparable sensitivity with the testing algorithm utilizing a GDH-and-toxin EIA and cell cytotoxicity neutralization assay. 11 A study was conducted for comparing the C. difficile toxin concentration in adults with symptomatic infection and asymptomatic carriage using the ultrasensitive quantitative immunoassay, which failed to yield any difference. 12 The GeneXpert, however, in our study did not detect any hypervirulent ribotype 027 strain.…”
Section: Discussionmentioning
confidence: 99%